Psychological distress among Afghan refugees in Norway as a function of their integration - Brea Larios, Dixie; Sam, David L.; Sandal, Gro Mjeldheim (Frontiers in Psychology, 2023)
Background Often, refugees are susceptible to mental health problems due to adversities experienced before, during, and after the flight. Through a cross-sectional study, the present study examines the relationship between different aspects of integration and psychological distress among Afghans living in Norway. Methods The participants were recruited through e-mail invitations, refugee-related organizations, and social media platforms. The participants (N = 114) answered questions about integration across multiple dimensions (psychological, social, navigational, economic, and linguistic) in line with the Immigration Policy Lab index (IPL -12/24). Hopkins symptoms checklist (HSCL-25) was used to assess psychological distress. Results Based on hierarchical multiple regression analysis, both the psychological dimension (0.269 p < 0.01) and the navigational dimension (0.358 p < 0.05) of integration predicted psychological distress. Discussion/Conclusion The results suggest that the psychological aspects of integration, such as being part of a community, having feelings of security, and a sense of belonging, are beneficial for the mental health and well-being of the Afghans in Norway and contribute further to other aspects of integration.